Reflections on Mental Health Advocacy Across Differing Ecological Levels - Nancy Thompson; Robin McGee; Elizabeth Walker; Leslie Munoz (Georgia Southern University, 2015)
Background: According to the World Health Organization, mental health advocacy is comprised of a range of actions designed to change aspects of attitudes and structures that impede the achievement of positive mental health in populations. Methods: According to the World Health Organization, mental health advocacy is comprised of a range of actions designed to change aspects of attitudes and structures that impede the achievement of positive mental health in populations. Results: We have proposed interventions and advocacy effort for each ecological level. Project UPLIFT, a distance-delivered intervention for mental health is presented as an example of an effort that can affect several levels of the social ecology. Conclusions: Advocacy and interventions that make an effort to encompass the levels of the social-ecological model may contribute to greater progress in improving mental health outcomes.